2014
DOI: 10.1002/pssr.201409408
|View full text |Cite
|
Sign up to set email alerts
|

Topological surface states of Bi2Te2Se are robust against surface chemical modification

Abstract: The robustness of the Dirac‐like electronic states on the surfaces of topological insulators (TIs) during materials process‐ing is a prerequisite for their eventual device application. Here, the (001) cleavage surfaces of crystals of the topological insulator Bi2Te2Se (BTS) were subjected to several surface chemical modification procedures that are common for electronic materials. Through measurement of Shubnikov–de Hass (SdH) oscillations, which are the most sensitive measure of their quality, the surface sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…A very recent XPS study clearly revealed that Bi 2 Te 3 and Bi 2 Te 2 Se easily form the corresponding oxides upon expose to air, while Bi 2 Se 3 was significantly more stable . Comparable findings were previously reported and also observed for Bi 2 Te 3 nanoparticles, which were shown to form bismuth oxides and tellurium oxides within a day upon expose to air …”
Section: Resultssupporting
confidence: 61%
“…A very recent XPS study clearly revealed that Bi 2 Te 3 and Bi 2 Te 2 Se easily form the corresponding oxides upon expose to air, while Bi 2 Se 3 was significantly more stable . Comparable findings were previously reported and also observed for Bi 2 Te 3 nanoparticles, which were shown to form bismuth oxides and tellurium oxides within a day upon expose to air …”
Section: Resultssupporting
confidence: 61%
“…Such a property has facilitated the detection of spin-polarized currents generated in this compound . As another advantage, the topological surface states of BTS have been documented to be robust against chemical surface modification including oxidation under ambient conditions . Furthermore, BTS can be grown in the form of nanowires or ribbons, which are required for high-density device integration. , This renders them into valuable test structures for the implementation of TIs into future information technology circuits.…”
mentioning
confidence: 99%
“…2,11−13 Yet, if new devices based on TIs, such as for spintronics and quantum computation, 2,14 are to be realized, addressing TIs through their surface chemistry must also be understood. 15,16 Indeed, precisely controlling the surface chemistry of TIs could be a prerequisite for interfacing them with other materials: Dirac states are highly surface-sensitive. 3,5 Absent packaging, a freshly cleaved sample of the TI would be exposed to air, and there are conflicting accounts as to the effects of such exposure on members of the Bi 2 (Te,Se) 3 family of TIs.…”
mentioning
confidence: 99%
“…These layers are separated by a van der Waals gap, 22 which allows in principle for facile cleavage along a basal plane leading to a terraced surface that can be visualized by atomic force microscopy (AFM). 16,18 A common method to cleave these materials is to align a sharp blade parallel to the basal (0001)…”
mentioning
confidence: 99%
See 1 more Smart Citation